2016
DOI: 10.1016/j.cct.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

“Watching time tick by…”: Decision making for Duchenne muscular dystrophy trials

Abstract: Objective This interview study explored clinicians’ perspectives and parents’ decision making about children’s participation in Duchenne muscular dystrophy (DMD) clinical trials. Methods Data from semi-structured interviews conducted with clinicians and parents in U.S. or Canada were assessed using thematic analysis. Results Eleven clinicians involved in ten trials and fifteen parents involved in six trials were interviewed. Parents described benefit-risk assessments using information from advocacy, peers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…We found that parents of children with FXS may be more risk averse to side effects compared with what has been observed in parents of children with lifethreatening conditions (Cartwright et al 2011;Deatrick et al 2002;Peay et al 2016). Parents of children with FXS, a chronic and stable condition, may be particularly resistant to risking their child's physical health.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…We found that parents of children with FXS may be more risk averse to side effects compared with what has been observed in parents of children with lifethreatening conditions (Cartwright et al 2011;Deatrick et al 2002;Peay et al 2016). Parents of children with FXS, a chronic and stable condition, may be particularly resistant to risking their child's physical health.…”
Section: Discussionmentioning
confidence: 56%
“…Parents of children with life‐threatening conditions, conversely, are faced with relatively little to lose in this domain, and medication side effects may be perceived as less harmful for their child when compared with the untreated disease course (Peay et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Health professionals who recruit should communicate the balance of benefits and risks associated with trial treatment, stressing negative physiological outcomes such as pain and fatigue. 272 Professionals should use questions and feedback to ensure that the child understands that they are participating in research, and that participation is voluntary; assent should be continuously renegotiated throughout the trial. 273 ii.…”
Section: Costs Borne By Patientsmentioning
confidence: 99%